Investigation of Electronic Parameters of Ag/N-Gap Schottky Barrier Diode - Dagdelen, Fethi; Ozer, Metin (Gazi Univ, 2015)
An Ag/n-GaP Schottky barrier diode was fabricated in vacuum with metal evaporating method. The electronic parameters were investigated by current-voltage (I-V) measurements at different temperatures. The electronic parameters such as ideality factor, barrier height and series resistance were determined from forward bias I-V measurement method and Cheung's functions at different temperatures. Results indicate that the barrier height of Ag/n-GaP diode increased with increase in temperature, while the ideality factor decreased. Ideality factor, barrier height and series resistance values are determined 2.01, 0.424 eV and 4.284 k Omega at 298 K, respectively.
Keywords: Schottky barrier; ideality factor; series resistance; n-GaP